2015
DOI: 10.1177/0883073815575575
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Against Disuse of the Masticatory System in Duchenne Muscular Dystrophy

Abstract: Duchenne muscular dystrophy patients report masticatory problems. The aim was to determine the efficacy of mastication training in Duchenne muscular dystrophy using chewing gum for 4 weeks. In all, 17 patients and 17 healthy age-matched males participated. The masticatory performance was assessed using a mixing ability test and measuring anterior bite force before, shortly after and 1 month after the training. In the patient group the masticatory performance improved and remained after 1-month follow-up, no si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
(71 reference statements)
0
15
0
2
Order By: Relevance
“…The gum chewing exercise has been used previously to improve bite force and masticatory function (Kiliaridis et al, 1995; Masumoto et al, 2009; Nakagawa et al, 2017; Ohira et al, 2012; van Bruggen et al, 2015). In this study, the mean MBF value of all subjects increased from 468 to 574 N after 4‐week chewing exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gum chewing exercise has been used previously to improve bite force and masticatory function (Kiliaridis et al, 1995; Masumoto et al, 2009; Nakagawa et al, 2017; Ohira et al, 2012; van Bruggen et al, 2015). In this study, the mean MBF value of all subjects increased from 468 to 574 N after 4‐week chewing exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, masticatory exercise seems important in improving masticatory disturbance and deficiency. It has been reported that gum chewing exercise is helpful in enhancing bite force and masticatory function (Kiliaridis, Tzakis, & Carlsson, 1995; Masumoto, Yamaguchi, & Fujimoto, 2009; Nakagawa et al, 2017; Ohira, Ono, Yano, & Takagi, 2012; van Bruggen et al, 2015). Kiliaridis et al (1995) reported that 4‐week training with hard chewing gum influenced the functional capacity of the masticatory muscles and increased their strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, negative correlation with the width and depth of the palate with tongue pressure in 11 patients with DMD was described [23]. A study by means of quantitative ultrasound of the oral muscles, sEMG, anterior tongue pressure, and videofluoroscopic swallowing (VFSS) showed progressive involvement of the muscles and swallowing problems with the first sign in the geniohyoid muscle during the ambulatory phase (ultrasound), tongue hypertrophy during the early and late non-ambulatory phase (ultrasound), increasing problems with solid food (VFSS), progressive decrease in tongue pressure, and lowest sEMG measurements in late nonambulatory phase [24].…”
Section: Mouth and Upper Airway Problems: Macroglossia Difficulties mentioning
confidence: 99%
“…35 patients from the cohort are still alive (aged 22-31 years); 18 died (aged [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Patients were ventilated by NIV (29/53) or IV (33/53).…”
Section: Causes Of Death and Ages Of Survival In Dmd What Is The Carmentioning
confidence: 99%